Handbook of Combustion 2010
DOI: 10.1002/9783527628148.hoc086
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Halocarbon Pyrolant Combustion

Abstract: Energetic materials are characterized by their ability to undergo a spontaneous highly exothermic reaction. They can be classified into high explosives (HEs), propellants, and pyrolants. High explosives upon initiation yield a detonation -that is a supersonic shock wave sustained by a chemical reaction. Propellants and pyrolants on the contrary undergo a thermally propagated reaction and yield either large amount of gaseous species, or in the case of pyrolants yield mainly condensed products. Unlike most high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…When first approaching the idea of electrospinning fibers and loading them with an energetic blend of n-Al and PFPE, Teflon AF was chosen as the likely precursor polymer to enable electrospinning of the suspension in order to maximize fluorine content of the bulk composite system. Pantoya et al showed that reaction of micrometer- and nanometer-sized aluminum blended with polytetrafluoroethylene (PTFE or Teflon) is driven to proceed by extraction of fluorine from the PTFE and formation of the thermodynamically stable species AlF 3 . This reaction is exothermic in nature and the reaction kinetics are well understood and extensively documented in the literature by numerous groups. ,− Teflon AF, a copolymer of Teflon, seemed like a logical choice for fiber fabrication because it is a solution processable, amorphous thermoplastic. However, in practice, Teflon and Teflon AF are not conducive to electrospinning because of their low dielectric constant values .…”
Section: Resultsmentioning
confidence: 99%
“…When first approaching the idea of electrospinning fibers and loading them with an energetic blend of n-Al and PFPE, Teflon AF was chosen as the likely precursor polymer to enable electrospinning of the suspension in order to maximize fluorine content of the bulk composite system. Pantoya et al showed that reaction of micrometer- and nanometer-sized aluminum blended with polytetrafluoroethylene (PTFE or Teflon) is driven to proceed by extraction of fluorine from the PTFE and formation of the thermodynamically stable species AlF 3 . This reaction is exothermic in nature and the reaction kinetics are well understood and extensively documented in the literature by numerous groups. ,− Teflon AF, a copolymer of Teflon, seemed like a logical choice for fiber fabrication because it is a solution processable, amorphous thermoplastic. However, in practice, Teflon and Teflon AF are not conducive to electrospinning because of their low dielectric constant values .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, PTFE mixtures with alternate metal fuels were developed. Among them, PTFE/Al mixtures have received significant attention as a reactive material formulation [ 19 ]. Aluminum nanoparticles, on account of their higher reactivity [ 20 ], have been progressively used as metal fuels in PTFE formulations as compared to the conventional micron-Al powders.…”
Section: Reactive Structures Based On Fluoropolymer-based Bindersmentioning
confidence: 99%